UTILIZING THE RESULTS OF UJIAN TAHAP BERSAMA AS SELF-REFLECTION FOR MEDICAL STUDENTS - Akbar, Resti Rahmadika; Garcia, Regilda; Khomeini, Khomeini (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Ujian Tahap Bersama is a form of formative exam initiated by AIPKI tomake students think and explore what they have learned. The results of the UjianTahap Bersama can be used as material for self-reflection by students to build,identify, and realize the extent of understanding of the knowledge that has beenobtained by students. This study aims to determine the utilization of the results of theUjian Tahap Bersama as material for self-reflection for students of the Faculty ofMedicine class of 2017 and 2018 at Universitas Baiturrahmah.Methods: This study used a mixed methods method that begins with a quantitativeand cross-sectional approach using secondary data. The results of the Ujian TahapBersama 1 and 2, namely the 2017 and 2018 batches and selected using a totalsampling technique using G-form to fill in the Graham Gibbs reflection of 30respondent. The results of Graham Gibbs' reflections were followed by in-depthinterviews with 7 respondents whose answers were not saturated.Results: Based on UTB marks the average ability of the 2018 class is higher thanthe 2017 class. The results of Graham Gibbs' reflection through the G-form showedthat students of the 2017 and 2018 batches were categorized into themes ofdescription, feelings, evaluation, analysis, conclusion, and action plan. The results ofthe in-depth interviews were categorized into positive and negative response themesusing Kirkpatrick 1 conceptConclusion: Based on the Kirkpatrick concept, the results of the UTB can be usedas material for reflection to improve student performance